Experimental philosophy and the problem of evil - Church, Ian M. (Religious studies, 2025)
The problem of evil is an ideal topic for experimental philosophy. Suffering - which is at the heart of most prominent formulations of the problem of evil - is a universal human experience and has been the topic of careful reflection for millennia. However, interpretations of suffering and how it bears on the existence of God are tremendously diverse and nuanced. Why does suffering push some people toward atheism while pushing others toward deeper faith? What cultural, psychological, or sociological differences account for this diversity of responses? And, importantly, what light might this diversity of responses shed on the problem of evil and how it has been formulated by philosophers in recent years? The aim of this article is to highlight how the tools and resources of experimental philosophy might be fruitfully applied to the problem of evil. In the first section, we review some recent work in this area and describe the current state of this emergent body of literature. In the second section, we review the broader and more recent theoretical developments on the problem of evil. In the final section, we outline some potential areas of future empirical research that we see as especially promising given those developments.